Accrual-based vs cash-based accounting in affecting underpricing phenomenon: Evidence from emerging country - Yuli Soesetio; Ely Siswanto; Lulu Nurul Istanti; Subagyo Subagyo (Jurnal Ekonomi Modernisasi, 2022)
Until now, more than 80 percent of shares are underpriced at every IPO event around the world, making it a phenomenon and a big unsolved puzzle, so it is still interesting and relevant to research, especially in emerging countries. This study aims to reveal the impact of profitability information based on accrual and cash on the phenomenon of underpricing on the Indonesia Stock Exchange (IDX). The sample used was firms that conducted IPOs on the IDX from 1994-2020 that had met the sample criteria of 475 firms using the purposive sampling method. Furthermore, the collected cross-section data were analyzed using ordinary least square (OLS) regression. The study concluded that only accrual-based profitability information consistently affects underpricing. These results also support the argument that the use of the accrual-based is better than the cash-based to predict underpricing. This study implies that IPO firms to pay more attention to, strengthen, and maintain their 'earnings' so that investors are more confident regarding the firm's future business continuity. In addition, investors are more detailed in using information from the prospectuses of large firms.